2021
DOI: 10.1002/smll.202006729
|View full text |Cite
|
Sign up to set email alerts
|

Binary and Ternary Colloidal Cu‐Sn‐Te Nanocrystals for Thermoelectric Thin Films

Abstract: Recent advances in copper chalcogenide-based nanocrystals (NCs), copper sulfide, and copper selenide derived nanostructures, have drawn considerable attention. However, reports of crystal phase and shape engineering of binary or ternary copper telluride NCs remain rare. Here, a colloidal hot-injection approach for producing binary copper/tin telluride, and ternary copper tin telluride NCs with controllable compositions, crystal structures, and morphologies is reported. The crystal phase and growth behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…At high enough Cu 1.5 Te concentrations, the formation of the Cu 2 SnTe 3 phase may also contribute to the charge transport by accepting electrons or facilitating the charge transport at the grain boundary. Notice in this regard that Cu 2 SnTe 3 is generally regarded as a low-carrier density semimetal . At the same time, the large grains generated in the presence of the Cu 2 SnTe 3 phase also contribute to the electrical conductivity but have little effect on the Seebeck coefficient …”
Section: Resultsmentioning
confidence: 99%
“…At high enough Cu 1.5 Te concentrations, the formation of the Cu 2 SnTe 3 phase may also contribute to the charge transport by accepting electrons or facilitating the charge transport at the grain boundary. Notice in this regard that Cu 2 SnTe 3 is generally regarded as a low-carrier density semimetal . At the same time, the large grains generated in the presence of the Cu 2 SnTe 3 phase also contribute to the electrical conductivity but have little effect on the Seebeck coefficient …”
Section: Resultsmentioning
confidence: 99%
“…Yang et al used tellurium oxide as a tellurium precursor to synthesize monodispersed nanocrystals of another similar material Cu 2 SnTe 3 [58]. Yin et al [59] synthesized different nanostructures such as Cu 1.29 Te nanocubes, nanosheets, and nanorods; Cu 1.43 Te hexagonal nanoplates; SnTe nanorods; and Cu 2 SnTe 3 nanocubes by carefully controlling the amount of tin precursor and reaction temperature in a colloidal synthesis method. B. Xu et al reported low-temperature and scalable (ca.…”
Section: Colloidal Synthesismentioning
confidence: 99%
“…Cation-deficient (self-doped) metal chalcogenide nanocrystals (NCs) exhibiting localized surface plasmon resonance (LSPR) have been extensively investigated as an infrared-responsive light-harvesting material. Cation-deficient copper chalcogenide NCs are typical members of the degenerately doped semiconductors family, which have attracted significant attention owing to their potential applications in thermoelectric, light-emitting, photovoltaic devices and photocatalysis. , Because such degenerated semiconductors exhibit dual nature of metals and semiconductors, the interplay between LSPR and band engineering is an important research issue. Illustrating the association between band engineering and LSPR tuning in such degenerated copper chalcogenides holds a key to further modulation of the cation-deficient copper chalcogenide NCs for suitable applications.…”
Section: Introductionmentioning
confidence: 99%